Evaluation of the correlation between KRAS mutated allele frequency and pathologist tumorous nuclei percentage assessment in colorectal cancer suggests a role for zygosity status. Issue 8 (27th April 2018) - Libbrecht, Louis; Baldin, Pamela; Dekairelle, Anne-France; Jouret-Mourin, Anne
Abstract : Evaluation of molecular tumour heterogeneity relies on the tumorous nuclei percentage (TNP) assessment by a pathologist, which has been criticised for being inaccurate and suffering from interobserver variability. Based on the 'Big Bang theory' which states that KRAS mutation in colorectal cancer is mostly homogeneous, we investigated this issue by performing a critical analysis of the correlation of the KRAS mutant allele fraction with the TNP in 99 colorectal tumour samples with a positive KRAS mutation status as determined by next-generation sequencing. Our results yield indirect evidence that the KRAS zygosity status influences the correlation between these parameters and we show that a well-trained pathologist is indeed capable of accurately assessing TNP. Our findings indicate that tumour zygosity, a feature which has largely been neglected until now, should be taken into account in future studies on (colorectal) molecular tumour heterogeneity.